Implementasi Pendidikan Agama Berbasis Pesantren di Kecamatan Baraka - Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The role of pesantren in giving birth to a quality generation is largely determined by the program implemented in the pesantren itself. Based on this view, the KKN student in Rambo Village, Baraka Enrekang endeavors to present various Muslim community development programs centered in Islamic boarding schools as a form of endeavor to improve the quality of civilization in Rambo village. The Umar bin Abdul Aziz Rumbo Islamic Boarding School became the center of activities for the Makassar STIBA KKN Students carrying out their program, namely Taklim Fiqh which was divided into two, namely around Imam Jurisprudence and around Jurisprudence on corpses, Basic training computers, and Teaching Aqidah Subjects.